Pengembangan Inovasi dengan Peningkatan Branding Usaha dan Pembukuan Secara Digitalisasi pada Pelaku UMKM “AA Bakery And Cake” di Kelurahan Mekarsari - Dewi Sartika; Maharani Syahputri; Lamria Siregar; Puput Halimatusa’diah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Field Work Practice (PKL) or also known as Innovation Development (PI) is a service activity of STIE Madani Balikpapan students to the community, especially to Micro, Small and Medium Enterprises (MSMEs). The MSME target for the Innovation Development Program in this group is AA Bakery and Cake which is located in RT 01 Mekarsari sub-district, Central Balikpapan District. The aim of this PI activity is to assist in creating innovation in terms of improving business branding in order to increase brand awareness among customers as well as assisting in creating digital financial reports.